Pendampingan Siswa-siswi Sekolah Menengah Pertama Taruna Islam Al-Kautsar Kraksaan dalam Mengenal Tingkah Laku Melalui Metode Ilmiah - Hasina Sabilah; Firdatus Sholeha; Endah Tri Wisudaningsih (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The main problem in this Community Service (PkM) activity is the condition of students at Al Kautsar Kraksaan Islamic Junior High School. They are in the puberty phase where emotional conditions are unstable. This situation results in problems in the form of negative social interactions, low motivation to learn, and social conflict within peer groups. For this purpose, the purpose of this PkM, we strive to provide educational and preventive assistance by increasing students' understanding of the application of scientific methods in studying behavior. In this case, we use the Participatory Action Research (PAR) method which invites students to actively collaborate with us in several important stages, namely: problem identification, action planning, evaluation, and reflection. The results of this activity show that students are able and even successful in using scientific methods to curb their behavior, in controlling emotions and rationally in making decisions in social life. This activity, in mentoring and participating in efforts to shape the character of students who are more responsible and ethical as well as more mature emotionally and socially.